Integration of Public Communication in the Perspective of Organizational Environment in Social Media - Suherman, Ansar; Hidayatullah, Muhammad; Filanti, Wa Ode Safnano; Ariendika, Rama (Universitas Muhammadiyah Ponorogo, 2025)
This research is motivated by the growing trend among various entities, including government organizations and private companies, in using social media platforms for communication strategies within the overall organizational environment. This phenomenon is widely regarded as a favourable development due to the inherent openness of the Web 2.0 environment, which allows for the dissemination of information and the facilitation of active engagement, discourse, and the creation of online communities. Nevertheless, the optimistic perspective on the advantages of social media communication in organizations ignores potential conflicts between the principles of openness associated with Web 2.0 and organizational management strategies and practices. This research aims to investigate the utilization of social media by several organizations in Indonesia. A qualitative approach was applied to generate the research findings by conducting in-depth interviews with informants from the research object and various social media specialists. These interviews aimed to explore methods for resolving conflicts between the nature of social media and organizations' strategic and managerial aspects. Specifically, this research focuses on addressing conflicts related to control and governance. The research results suggest a potential path for further exploration in the field of public communication, particularly in aligning organizational goals with the needs of online communities.